A novel essential splice site variant in SPTB in a large hereditary spherocytosis family. Issue 5 (4th May 2021) - Nieminen, Taina T.; Liyanarachchi, Sandya; Comiskey, Daniel F.; Wang, Yanqiang; Li, Wei; Hendrickson, Isabella V.; Brock, Pamela; de la Chapelle, Albert; He, Huiling
Abstract: Background: We studied a large family with 22 individuals affected with autosomal dominant hereditary spherocytosis (HS). Methods: Genome‐wide linkage, whole‐genome sequencing (WGS), Sanger sequencing, RT‐PCR, and ToPO TA cloning analyses were performed. Results: We revealed a heterozygous G>A transition in the 14q23 locus, at position +1 of the intron 8 donor splice site of the spectrin beta, erythrocytic ( SPTB ) gene. This splice variant ( SPTB c.1064+1G>A) was confirmed by Sanger sequencing and showed complete co‐segregation with HS in the family. Further RT‐PCR reactions and sequencing analysis indicated that the variant leads to the exclusion of exon 8 and subsequent frameshift in exon 9 and a premature stop codon in SPTB . Translation of the altered allele would lead to a truncation with a loss of all spectrin repeat domains in SPTB protein. Conclusion: This variant is novel and has not been found in any databases. We propose that this splice variant explains the spherocytosis phenotype observed in this large family. Abstract : We studied a large family with 22 individuals affected with autosomal dominant hereditary spherocytosis (HS). Genome‐wide linkage and whole‐genome sequencing analyses revealed a heterozygous G>A transition in the 14q23 locus, at position +1 of the intron 8 donor splice site of the spectrin beta, erythrocytic ( SPTB ) gene.